2016
DOI: 10.1021/acs.jpcc.6b00402
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Simulation Studies of the Stepped Adsorption of Toluene on Pure-Silica MEL Zeolite

Abstract: In this work, the adsorption of toluene on puresilica MEL zeolite is investigated using a variety of experimental and simulation methods. First, we measured the volumetric and calorimetric isotherms at 301 K and at 315 K. The volumetric adsorption isotherm presents a substep at a loading of roughly 4 molecules per unit cell that shifts to higher pressures at higher temperatures and that coincides with a sudden increase in the isosteric heat of adsorption. Grand canonical Monte Carlo simulations reveal that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…The alkyl chain of ethanol is large enough to favor an adsorption that seems to be more energetic when zigzag channels are present (see Figure 4 and Table 1 below to compare the heats of adsorption). Since intersections are first occupied in the adsorption processes in this type of zeolites, 35 this seems an indication that the zigzag channel intersections should be more energetic than those of linear channels present in MEL. These effects are not visible at all in 1-butanol, whose adsorption is completely dominated by steric effects given its larger molecular size as compared with both MEL and MFI channels.…”
Section: ■ Resultsmentioning
confidence: 99%
“…The alkyl chain of ethanol is large enough to favor an adsorption that seems to be more energetic when zigzag channels are present (see Figure 4 and Table 1 below to compare the heats of adsorption). Since intersections are first occupied in the adsorption processes in this type of zeolites, 35 this seems an indication that the zigzag channel intersections should be more energetic than those of linear channels present in MEL. These effects are not visible at all in 1-butanol, whose adsorption is completely dominated by steric effects given its larger molecular size as compared with both MEL and MFI channels.…”
Section: ■ Resultsmentioning
confidence: 99%
“…The X-ray powder diffraction patterns of both as-received and calcined Beta25, Beta38 and Beta360, before and after saturation with TOL are reported in Figure 4. By comparing the X-ray powder diffraction pattern of both the as-received and the calcined materials before and after TOL adsorption (see Figure 4) it can be observed that the peaks intensities in the low 2θ region change thus confirming the incorporation of molecules in the framework due to adsorption, moreover the differences in the patterns in the intermediate and high 2θ region indicates that the process is associated with the framework flexibility (expansion or contraction of the cell volume) [42,43]. Similar behaviour is also shown when the three zeolite samples before and after thermal treatment are compared.…”
Section: Thermal and Structural Analysesmentioning
confidence: 99%
“… 37 , 38 Many industrial applications strongly rely on the selective hosting capabilities of zeolites. 39 − 44 …”
Section: Introductionmentioning
confidence: 99%
“… 73 − 75 Several studies where MCs are used to study adsorption of aromatics in zeolites can be found in the literature. 44 , 76 86 Most molecular simulation studies of adsorption of hydrocarbons in zeolites have focused on adsorption from a vapor phase. 78 This is due to the difficult insertion and deletion of molecules at conditions close to saturation, leading to inefficient simulations.…”
Section: Introductionmentioning
confidence: 99%